Uji Aktifitas Daya Hambat Ekstrak Daun Jambu Biji (Psidium Guajava) Terhadap Pertumbuhan Bakteri Streptococcus Mutans - Ramadhan, Willy Syahrina; Elfia, Linda; Iisniawati, Iisniawati (Universitas Sumatera Barat, 2025)
Dental caries is a common oral health problem caused by Streptococcus mutans, a bacterium that ferments carbohydrates into acid and damages tooth enamel. The high prevalence of dental caries in Indonesia highlights the need for natural antibacterial alternatives. Guava (Psidium guajava) leaf contains flavonoids, tannins, and saponins that have antibacterial potential. This study aims to determine the inhibitory effect of ethanol extract of guava leaves on Streptococcus mutans at concentrations of 1.25%, 2.5%, and 5%. The research used a laboratory experimental method with a Completely Randomized Design (CRD). Extraction was performed using maceration with 96% ethanol, while antibacterial testing used the disc diffusion method. The results showed inhibition zones at all concentrations, with the strongest inhibition at 5%. These findings indicate that guava leaf extract may serve as a natural antibacterial agent for preventing dental caries.